KELALAIAN (NEGLIGENCE) DAN MALPRAKTIK MEDIS - Siti Rokayah; Gunawan Widjaja (Cross-border, 2022)
This research aims to change the stigma that exists in society regarding negligence and medical malpractice carried out by doctors against patients which can be considered as criminal acts and or acts against the law. This research is a descriptive normative research, and uses a prescriptive form with the aim of problem solution. The results of this research indicate that negligence and medical malpractice arise from a contractual relationship or agreement between a patient and a doctor, in which case the doctor suspected of negligence and medical malpractice is qualified to have breach of contract.